P58 A review of hepatitis C testing in a district general hospital – a case for testing cocaine users and sexual contacts of HIV negative hepatitis c patients?. (18th May 2015) - Oliver, Rebecca; Gupta, Nadi
Abstract : Background/introduction: Hepatitis C has significant public health consequences and substantial morbidity and mortality. Timely identification and treatment is needed to avert the rising prevalence of Hepatitis C related chronic liver disease. There is currently an inconsistency in the guidance for which groups to screen, with BASHH and Public Health UK recommending slightly differing protocols. Aim(s)/objectives: The aim of this project was to audit Hepatitis C testing in the Rotherham GU medicine clinic against the standards set out by the Public Health England Migrant Health Policy. Methods: All hepatitis C antibody positive diagnoses between January 2010 and May 2014 were identified. A retrospective case note review was undertaken to ascertain the indication for hepatitis C testing. Results: 25/27 of the hepatitis C positive patients were tested for a reason recommended by the Public Health England guidelines: Discussion/conclusion: Two of the patients were tested for reasons other than those listed by Public Health England and BASHH guidance. The issue of hepatitis C testing in cocaine users and HIV negative heterosexual contacts is currently under scrutiny by Public Health England and NICE, however neither advocates testing based upon these. Our audit data suggests that hepatitis C testing may be advisable in intranasal cocaine users and sexual contacts of hepatitis C. There are epidemiological studies to support these findings.